Plerixafor added to G‐CSF allows mobilization of a sufficient number of hematopoietic progenitors without impacting the efficacy of TCR‐alpha/beta depletion in pediatric haploidentical and genoidentical donors failing to mobilize with G‐CSF alone. Issue 4 (8th March 2021) - Kurnikova, Elena; Trakhtman, Pavel; Pershin, Dmitry; Ilyushina, Mariya; Khismatullina, Rimma; Maschan, Michael; Novichkova, Galina; Maschan, Alexey
Abstract: Background: Collection of a large number of early hematopoietic progenitors is essential for allogeneic apheresis products intended for TCR‐alpha/beta depletion. Materials and Methods: We added plerixafor 0.24 mg/kg body weight (bw) on day 4 of high‐dose filgrastim mobilization 10 hours prior to apheresis in 16 (30.5%) pediatric allogeneic donors who failed to recover a sufficient number of CD34+ cells. Results: On day 4 of G‐CSF, the median CD34+ cell count in peripheral blood was 6 per μL (range 4‐9 per μL) in 6 poor mobilizers and 16 per μL (range 12‐19 per μL) in insufficient mobilizers. In all donors, the threshold of 50 CD34+ cells/μL was achieved, and the median increase was 14.8‐fold in poor mobilizers and 6.5‐fold in insufficient mobilizers, whereas it was 3.45‐fold increase in those mobilized with G‐CSF alone. Discussion: In all donors, a predefined number of >10 × 10 6 CD34+ cells/kg of recipient bw before depletion was reached in the apheresis product. The use of plerixafor did not affect the purity of further TCR‐alpha/beta depletion. Side effects were mild to moderate and consisted of nausea and vomiting. Conclusion: Thus, the safety and high efficacy of plerixafor was proven in healthy pediatric allogeneic hematopoietic cell donors.